PERFORMANS BURUNG PUYUH (Coturnix – coturnix japonica) YANG DIBERIKAN TEPUNG KEONG SAWAH (Pila ampullacea) SEBAGAI PENGGANTI TEPUNG IKAN DALAM RANSUM - The, Fransela; Sarajar, Ch. L. K.; Montong, M. E. R.; Najoan, M. (ZOOTEC, 2017)
PERFORMANS OF QUAIL (Coturnix – coturnix japonica) PROVIDED CONCH PADDY (Pila ampullacea) FLOUR AS A SUBSTITUTE FOR FISH FLOUR IN THE RATION. This research aims to determine the extent to which the use of conch paddy (Pila ampullacea) flour as a substitute for fish flour in the ration on the performances of Quail (Coturnix- Coturnix japonica). This research used 60 quail 5-week-old female and for data collection was performed 8 weeks. The design used was a completely randomized design (CRD), which consists of 4 treatments and 5 replications. Such treatment is the conch paddy flour with some level of giving in the ration, which is : R0 = 0% conch paddy flour + 15% fish flour, R1 = 5% conch paddy flour + 10% fish flour, R2 = 10% conch paddy flour + 5% fish flour, and R3 = 15% conch paddy flour + 0% fish flour. Variables measured in order to see the response of quail to the conch paddy flour is feed consumption, egg production and feed conversion. Results of analysis of variance showed that the treatment was not significantly different on feed consumption, egg production and feed conversion. Based on the results of this research indicate conch paddy flour up to the level of 15% can be used as a substitute for fish flour in the ration of quail. Keywords : quail, conch paddy, performances, and fish flour